Tanggungjawab Atas Kerugian pada Kerja Sama Usaha Ternak Ayam Boiler dengan PT. Japfa Comfeed Ditinjau dari Kompilasi Hukum Ekonomi Syariah: Studi Kasus di Dusun Kerpai Kecamatan Selesai Kabupaten Langkat - Annisa Putri Sahara; Uswatun Hasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This case began with the implementation of boiler chicken cultivation cooperation between PT. Japfa Coveed with its cooperation partners. PT. Japfa Comveed has entered into a cooperation agreement with partners, one of which is to support the health and quality improvement of the chicken. In fact, the agreement was not implemented at all and only demanded sales targets. In this study, the author formulated a study on the implementation of the shirkah contract in the risk sharing agreement between PT Japfa Comfeed and partners in Kerpai Hamlet, Finish District, Langkat Regency, the factor that PT Japfa Comfeed does not want to be responsible for the partners that occur in Kerpai Hamlet, Finish District, Langkat Regency, and the responsibility for the losses made by PT Japfa Comfeed to partners in boiler chicken cultivation reviewed from the Compilation of Sharia Economic Law in Kerpai Hamlet, Selesai District, Langkat Regency. This study uses an empirical method. The empiric method is a research method that uses data from the field and direct research to get accurate data. This empirical research is used to make it easier for writers. The results of this study prove that the responsibility carried out by PT japfa Comfeed itself is not in accordance with Kompilasi Hukum Ekonomi Syariah (KHES). This is because Japfa Comfeed itself deliberately reduces its obligations to its partners by not fulfilling the responsibilities that have been previously agreed. This is done to reduce partial losses felt by the company. This accountability has never been carried out by PT Japfa Comfeed so that as a result partners suffer losses ranging from inappropriate chicken weights, health conditions of cages and shirkah objects, to not being able to compete in the regional and regional markets.